Paperwork, compassion and temporal conflicts in British social work. (November 2019) - Yuill, Chris; Mueller-Hirth, Natascha
While previous literature has examined time discourses in social work and demonstrated that social work is predicated on linear understandings of time, one area that has received little theoretical and empirical attention in the literature on time and social work is what effects various social work temporalities exert on the lifeworld of social workers and how they shape their working days. This paper draws on semi-structured interviews with British social workers and employs an abductive approach to data analysis. By analysing the participants' experiences of time and work, the article identifies two temporalities that exist in social work practice, paperwork time and compassionate time. Paperwork time is linear, instantaneous and accelerated, requiring social workers to juggle multiple competing demands and needs. Compassionate time is more developmental and cyclical and requires slower engagement. The paper then discusses how social workers negotiated these contradictory temporalities and highlights the potentially negative effects of temporal conflicts on people's health, well-being and on social work practice at large.